Images of violence. Representation of women in ’Crime and Justice’ News in digital newspaper ’crhoy.com’ in Costa Rica in 2017 - Martínez Toledo, Yanet (Estudios sobre el Mensaje Periodístico, 2020)
The current article develops an analysis of images published in Costa Rican digital newspaper crhoy.com in 2017. Its purpose is to investigate the role of images (photographs, infographics, videos) in the construction of news about violence against women. The interest in this topic arose in previous studies by the author (Autor y Jiménez, 2016; Autor, 2018; Autor, 2018b). The methodological approach is both qualitative and quantitative. In the quantitative phase, the principal goal was to identify types of violence against women represented in the news, also actors, and authors of the images. The qualitative research allowed to understand the visual rhetorics strategies such as the symbolic representation of the location, women agency, institutional actions to prevent and eradicate violence against women (Gries, 2015). The results reveal that women are scarcely represented as agents in the news, but rather as passive victims of violence (Mulvey, 2011). There is a media usage of ´politics of pity´ (Chouliaraki, 2006, p. 53) as a rhetorical strategy in the representation of victims.